Microencapsulation by spray drying of the Lactobacillus plantarum P2 for potential application as a probiotic - Chagas, Viviany Santos; Tarabal, Vinícius Souza; Silva, Felipe Ferreira; Meira, Hiure Gomes Ramos; Parreira, Adriano Guimarães; Silva, José Antônio da; Magalhães, Juliana Teixeira de; Granjeiro, Paulo Afonso; Oliveira, Letícia Fernandes de; Gonçalves, Daniel Bonoto (Food Science and Technology, 2025)
Probiotics are microorganisms that, when ingested in adequate amounts, confer benefits to the organism. The biggest concerns with these products are storage, stability, and survival of the microorganisms that make up these products. Spray-drying processes are an excellent alternative for drying these products because, through microencapsulation, the stability, survival, and resistance to gastric juice and bile salts are preserved. This work evaluated the influence of entry temperature and arabic gum concentration in the spray drying of Lactobacillus plantarum P2. Encapsulated cells were characterized for survival, resistance to gastrointestinal conditions, and particle morphology. Both parameters significantly impacted the spray-drying process. An increase in arabic gum concentration resulted in a higher survival rate, while elevated temperatures caused a reduction in survival rates. As for the resistance response to gastrointestinal conditions, only the quadratic temperature was statistically significant. By scanning electron microscopy, we observed the microencapsulation of the microorganism. An optimum estimated point was reached for drying the P2 strain at an entry temperature of 105°C and an arabic gum concentration of 21%, obtaining a process with a higher survival rate and better resistance to gastrointestinal conditions, reinforcing the potential application of this microorganism as a probiotic.